Genomic structural variation-mediated allelic suppression causes hybrid male sterility in rice - Rongxin Shen (Nature Portfolio, 2017)
A reproductive barrier between japonica and indica rice subspecies hinders hybrid breeding. Here, the authors reveal that structural and copy number variations of a pollen-essential gene, which encodes a DUF1618-domain protein, result in allelic suppression and subsequently cause hybrid male sterility.